The role of the Internal Audit Department in detecting corruption through accountability (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Internal Audit  is one of the most important backers of corporate governance, the researcher expanded his interest in this subject to examine the efficiency of Internal Auditors at the Arab Bank and its branches in Jordan to achieve Accountability which enhances the Corporate Governance and to identify the effect of the International Internal Audit  Standards in strengthening the role of Internal Auditors in Accountability, and the effect of Attribute and Performance Standards in Accountability. The researcher applied descriptive analysis method to define the role of Internal Audit in the Arab Bank in achieving one of the basic principles of Corporate Governance assimilated in Accountability. The researcher’s sources include books, scientific references and academic research in addition to previous studies as secondary sources. The primary source is the survey which is used to achieve the basic objectives of this study.   Moreover, the researchers used an appropriate statistical method to test the hypothesis   The study found that Internal Audit Standards (Attribute and Performance Standards) explain 53.6% of the changes in the Internal Auditor's role in Accountability in the Arab Bank, while the Attribute Standards have the major role in those changes, while independency and objectivity form the cornerstone for achieving Accountability.